2022
DOI: 10.3390/ma15134468
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Angiogenesis and Cell Survivability of an Inkjet Bioprinted Biological Implant in an Animal Model

Abstract: The rapidly growing field of tissue engineering hopes to soon address the shortage of transplantable tissues, allowing for precise control and fabrication that could be made for each specific patient. The protocols currently in place to print large-scale tissues have yet to address the main challenge of nutritional deficiencies in the central areas of the engineered tissue, causing necrosis deep within and rendering it ineffective. Bioprinted microvasculature has been proposed to encourage angiogenesis and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The orifice of the inkjet print head allows single cells to pass through after being subjected to high-energy sources (Figure 2B). 84 Thermal inkjet printing was the first technology that was used for bioengineering applications with protein arrays and DNA chips as the first bioprinting products. [87][88][89] Following these successes, printing bacteria and mammalian cells with high viability rates paved the way for a wider range of applications.…”
Section: Emerging Cell-based Bioengineering Technologies For Pad Trea...mentioning
confidence: 99%
See 2 more Smart Citations
“…The orifice of the inkjet print head allows single cells to pass through after being subjected to high-energy sources (Figure 2B). 84 Thermal inkjet printing was the first technology that was used for bioengineering applications with protein arrays and DNA chips as the first bioprinting products. [87][88][89] Following these successes, printing bacteria and mammalian cells with high viability rates paved the way for a wider range of applications.…”
Section: Emerging Cell-based Bioengineering Technologies For Pad Trea...mentioning
confidence: 99%
“…[87][88][89] Following these successes, printing bacteria and mammalian cells with high viability rates paved the way for a wider range of applications. 90 For example, Oropeza et al 84 demonstrated the ability to print human microvascular ECs using a modified inkjet bioprinter and successfully implanted the constructs into a murine model, resulting in a significant increase in the vascular formations in the implant area (Figure 2C). 91 Advances in 3D printing have led to the development of new approaches to treat PAD, specifically in generating large tissue-engineered vascular graft replacements.…”
Section: Emerging Cell-based Bioengineering Technologies For Pad Trea...mentioning
confidence: 99%
See 1 more Smart Citation
“…In an innovative approach, the utilization of bioprinted microvasculature has been suggested as a means to foster angiogenesis and enhance the diffusion of essential oxygen and nutrients throughout engineered tissue constructs. [ 213 ] An implant, created using thermal IJP, featured HMVECs and was strategically placed within both CB17severe combined immunodeficient (CB‐17 SCID; i.e., strain bred mice that lack functional T and B cells) and NSG‐SGM3 (i.e., non‐obese diabetic SCID gamma mice with human stem cell factor, granulocyte macrophage colony stimulating factor and interleukin‐3) animal models. This strategic positioning aimed to assess the kinetics of angiogenesis and the extent of cell viability.…”
Section: Bioprintingmentioning
confidence: 99%